Zeller, Benjamin E., ed. 2001. Handbook of UFO Religions - Lutkajtis, Anna (Fieldwork in Religion, 2022)
Zeller, Benjamin E., ed. 2001. Handbook of UFO Religions. Leiden and Boston, MA: Brill. xvii + 542 pp. ISBN: 978-90-04-43437-0 (hbk). €199.00.